How Does the Spirit of Capitalism Affect Stock Market Prices? - Smith, William T. (Review of Financial Studies, 2001)
Bakshi and Chen (1996b) suggest that the spirit of capitalism affects stock prices by increasing society's aversion to risk. In this article, I show that the way in which the spirit of capitalism impinges upon asset prices depends on the interaction of impatience, willingness to substitute over time, and ordinal preferences between consumption and status, in addition to risk aversion. I develop a general model that charts the channels through which the spirit of capitalism affects asset prices. An increase in the capitalist spirit may increase or decrease risk aversion, and may actually decrease the prices of risky assets.